METHODS OF TEACHING METAPHORS - Rajabov Feruz (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: The article discusses the role of metaphors in English as a Second Language (ESL) acquisition, emphasizing their importance in enhancing learners’ reading, vocabulary retention, and critical thinking skills. It highlights common challenges, such as cultural differences in metaphorical imagery and teachers’ tendency to underestimate the value of metaphor instruction. The authors argue that metaphors should be integrated into vocabulary teaching, as they are part of everyday communication and essential for developing communicative competence. Various techniques are suggested for different proficiency levels, including matching exercises, metaphor identification in argumentative texts, creative rephrasing, and using advertising materials to foster metaphor awareness. The study underlines that working with metaphors not only strengthens language skills but also promotes cross-cultural understanding, creativity, and critical evaluation.